Case Report: Plasticity in Central Sensory Finger Representation and Touch Perception After Microsurgical Reconstruction of Infraclavicular Brachial Plexus Injury - Ernst, Jennifer; Weiss, Thomas; Wanke, Nadine; Frahm, Jens; Felmerer, Gunther; Farina, Dario; Schilling, Arndt F.; Wilke, Meike A. (Frontiers in Neuroscience, 2022)
After brachial plexus injury (BPI), early microsurgery aims at facilitating reconnection of the severed peripheral nerves with their orphan muscles and sensory receptors and thereby reestablishing communication with the brain. In order to investigate this sensory recovery, here we combined functional magnetic resonance imaging (fMRI) and tactile psychophysics in a patient who suffered a sharp, incomplete amputation of the dominant hand at the axilla level. To determine somatosensory detection and discomfort thresholds as well as sensory accuracy for fingers of both the intact and affected hand, we used electrotactile stimulation in the framework of a mislocalization test. Additionally, tactile stimulation was performed in the MRI scanner in order to determine the cortical organization of the possibly affected primary somatosensory cortex. The patient was able to detect electrotactile stimulation in 4 of the 5 fingertips (D1,D2,D4,D5), and in the second phalanx in D3 indicating some innervation. The detection and discomfort threshold were considerably higher at the affected side than at the intact side, with higher detection and discomfort thresholds for the affected side. The discrimination accuracy was rather low at the affected side, with stimulation of D1/D2/D3/D4/D5 eliciting most commonly a sensation at D4/D1/D3/D2/D5, respectively. The neuroimaging data showed a mediolateral succession from D2 to D5 to D1 to D4 (no activation was observed for D3). These results indicate a successful regrowth of the peripheral nerve fibers from the axilla to four fingertips. The data suggest that some of the fibers have switched location in the process and there is a beginning of cortical reorganization in the primary somatosensory cortex, possibly resulting from a re-education of the brain due to conflicting information (touch vs. vision).